The influence of percieved value and percieved quality on revisit intention with satisfaction as a mediating variable - Adelya Asidiqhi; Yasri Yasri (Marketing Management Studies, 2022)
The study aims to analyze the influence of Perceived Value and Perceived Quality on Revisit Intention with Satisfaction as mediation on visitors to The Balcone Hotel. This type of research is explanatory. The population of this study is visitors to The Balcone Hotel who have visited the hotel at least once. The study sample was 210 respondents. The study used a structural equation model (SEM) test with smart-PLS 3.0 software. The results of this study include: (1) Satisfaction negatively affects Revisit Intention. (2) Perceived Quality has a positive effect on satisfaction. (3) Perceived Value has a positive effect on satisfaction. (4) Perceived Quality has a positive effect on Revisit Intention. (5) Perceived Value negatively affects Revisit Intention. (6) Perceived Quality has a positive effect on Perceived Value. (7) Perceived Value negatively affects Revisit Intention mediated by Satisfation. (8) Perceived Quality negatively affects Revisit Intention mediated by Satisfaction.